1999
DOI: 10.1128/jcm.37.10.3353-3356.1999
|View full text |Cite|
|
Sign up to set email alerts
|

Case of Staphylococcus schleiferi Endocarditis and a Simple Scheme To Identify Clumping Factor-Positive Staphylococci

Abstract: Staphylococcus schleiferi is a coagulase-negative staphylococcus infrequently reported as a human pathogen. We report a case of prosthetic valve endocarditis attributed to this organism, contrast it to another Staphylococcus species that gives similar clumping factor results (S. lugdunensis), and propose a simple, effective identification scheme for identification of clumping factor-positive staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
(12 reference statements)
0
24
0
2
Order By: Relevance
“…Though it is primarily a veterinary pathogen, S. schleiferi can also cause opportunistic infections in humans. Cases of endophthalmitis (22), endocarditis (23,24), bacteremia (25), osteomyelitis (26), and wound (27), surgical site (27), and pacemaker (28) infections have been reported. S. schleiferi was implicated in an outbreak of surgical site infections and was originally misidentified as Staphylococcus aureus (29).…”
mentioning
confidence: 99%
“…Though it is primarily a veterinary pathogen, S. schleiferi can also cause opportunistic infections in humans. Cases of endophthalmitis (22), endocarditis (23,24), bacteremia (25), osteomyelitis (26), and wound (27), surgical site (27), and pacemaker (28) infections have been reported. S. schleiferi was implicated in an outbreak of surgical site infections and was originally misidentified as Staphylococcus aureus (29).…”
mentioning
confidence: 99%
“…They can be distinguished by activity of tube coagulase and urease. S. schleiferi subsp schleiferi is tube coagulase and urease negative, whereas S. schleiferi subsp coagulans is tube coagulase and urease positive [6].…”
Section: Case Reportmentioning
confidence: 95%
“…S. schleiferi has shown diverse human involvement including infection of pacemaker wires, endocarditis, extradural abscesses, and meningitis [6,7]. A retrospective study on 28 patients with S. schleiferi infection found that this pathogen was most commonly involved with surgical wound infections.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…A high rate of false identification by phenotypic methods has been reported in Nigeria contributing to 85% misidentification of S. aureus, whereas 49% false identification has been documented in Libya [49] [50]. Although coagulase test represents the standard method for identification of S. aureus, a few CoNS produce clumping factor which can be erroneously interpreted as coagulase-positive S. aureus [51] [52]. Due to budgetary and time constraints, further experiments were not carried out to verify the identity of these isolates.…”
Section: Amplification Of Vick Genementioning
confidence: 99%